Effective Learning Style: The Key to Success in the Education Process - Izza, Nadhira Nurul; Mahmud, Salami; Fadli, Fatmawati; Dewi, Rini Liana (FITRAH: International Islamic Education Journal, 2025)
An effective learning process requires an approach that accommodates the diversity of student learning styles, including those with high intellectual intelligence (IQ) who may not yet recognize their optimal way of learning. Each individual has a different way of absorbing, processing, and storing information, making the understanding of learning styles a crucial aspect in education. This study aims to identify effective learning styles, particularly for students with high intellectual intelligence (IQ) who have not yet understood their appropriate learning style, and to analyze various factors that influence learning success. This research uses a library research method by analyzing recent scientific literature. The findings indicate that visual, auditory, and kinesthetic learning styles can all enhance learning effectiveness when integrated with appropriate teaching strategies, high learning motivation, and a conducive learning environment. Teachers play a central role in recognizing student characteristics and adapting their teaching approach accordingly. Understanding learning styles not only impacts academic achievement but also creates a more personalized, inclusive, and adaptive learning atmosphere. This study highlights the importance of a holistic approach in education, involving the interconnection between learning styles, intellectual potential, teaching strategies, and the learning environment to realise a higher-quality education system that is responsive to each learner's needs. This research contributes a novel perspective by focusing on the group of high-IQ students and advocating for the integration of individualized learning styles into classroom practice to achieve a more inclusive, adaptive, and high-quality education system.